The yield of EUS‐FNA in undiagnosed upper abdominal adenopathy is very high. Issue 4 (12th December 2012) - Coe, Adam; Conway, Jason; Evans, Jerry; Goebel, Michael; Mishra, Girish
Abstract Purpose: Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) allows sampling of abdominal adenopathy easily and safely from locations that were previously deemed too risky and inaccessible. The efficacy of EUS‐FNA in a large cohort of patients with abdominal adenopathy has not been previously described in the literature. Methods: We conducted a large retrospective study at a tertiary referral center. Two hundred twenty‐five consecutive patients undergoing EUS‐FNA for only abdominal adenopathy between 2004 through August 2009 were included in our study. Patient demographics, indications, EUS findings, and final cytologic diagnoses were recorded. Results: A total of 230 lymph nodes were biopsied in 225 patients. Common locations of nodes included peripancreatic (19%), porta hepatis (18%), and celiac axis (18%). Adequate specimens were obtained in 200/230 nodes (87%) and the most common diagnoses based on cytology were: benign/reactive (50%), adenocarcinoma (20%), lymphoma (8%). The sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy were 71%, 99%, 99%, 78%, and 85%, respectively, for EUS‐FNA. Based on EUS imaging alone, malignant nodes were more likely to be larger in diameter (17 mm versus 26 mm, p < 0.001), have a round shape (p = 0.002), well‐defined borders (p = 0.04), and hypoechic echotexture (p < 0.001). Conclusions: EUS‐FNA allows for excellent tissue acquisition in abdominal lymphadenopathy. Our study supports the use of traditional EUS imaging criteria to identify suspected malignant adenopathy. The results from our large cohort of patients show that EUS‐FNA should be considered as a first‐line diagnostic modality for ascertaining the etiology of abdominal lymphadenopathy. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013